HADITH ANALYSIS OF THE PROHIBITION OF WOMEN GOING OUT AT NIGHT WITHOUT A MAHRAM: A STUDY OF SOCIAL FACTORS - Mohd Nazri; Ilham Abiyusuf; Syifa Qalbina; Laila Sari Masyhur (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the hadith prohibiting women from going out at night without a mahram, focusing on the social factors underlying this prohibition and its impact on the social life of Muslim women. This issue is important as it relates to the understanding of women's roles in society and the boundaries set by religion. The methodology used is a qualitative approach with a case study type of research, allowing for an in-depth understanding of the social and cultural context surrounding this hadith. The findings indicate that this prohibition serves as a protective measure for women, reflects family responsibility, and maintains the honor and dignity of women in society. Although social contexts and security have changed, the principles contained in this hadith remain relevant in building a safe society that respects women's rights. This research is expected to contribute to a broader understanding of women's roles in Islamic society and open new insights into the relationship between religious texts and the evolving social realities.